Numerical analysis on natural convection heat transfer of a heat sink with cylindrical pin fin [electronic resource] - Yap, Zi Qin, 1989-; Amer Nordin Darus; Fakulti Kejuruteraan Mekanikal (2013)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2013